Work Stress and Work Motivation on Employee’s Turnover Intention Mediated by Organizational Commitment - Arief, Sartika Wati HS; Sudiro, Achmad; Djumahir, Djumahir (Interdisciplinary Social Studies, 2022)
Background: With limited space to work WFH during the pandemic, it is the biggest challenge faced by all employees and companies.  In the midst of many companies holding a hiring freeze policy  or temporarily suspending the recruitment of new employees, ruangguru even did the opposite, RuangGuru held a routine recruitment of new employees during the pandemic. Aim: This study aims to analyze and explain the effect of work stress and work motivation on turnover intention mediated by organizational commitment of employees of FEC PT.  Ruang Raya Indonesia Sumapapua I Makassar, Pare-Pare, Palopo. Method: This type of research is an explanatory research that explains the causal relationship between the variables used through hypothesis testing. The sampling method in this study uses the saturated sampling method. The population determined in this study was 108 people, namely all employees of FEC Sumapapua I covering the Makassar, Pare-Pare, Palopo areas. The data obtained from the sample were analyzed using Structural Equation Modeling (SEM) analysis, with the SMARTPLS 3.0 approach. Findings: The results showed that work stress has a positive and significant effect on turnover intention, work motivation has a negative and significant effect on turnover intention, work stress has a negative and significant effect on organizational commitment, work motivation has a positive and significant effect on organizational commitment, organizational commitment has a negative and significant effect on organizational commitment turnover intention, organizational commitment does not mediate the effect of work stress on turnover intention, organizational commitment mediates the influence of work motivation on turnover intention.